As the crow flies: Conventions and symbolism in Seven Minutes in the Warsaw Ghetto. Issue 2 (1st October 2014) - Shaw, Nathan
In feature-length Holocaust cinema, viewers witness two hours of harrowing events, before being pacified with an ending providing some comfort and relief; often undermining what has gone before. However, in short-film Seven Minutes in the Warsaw Ghetto, this structure is reversed, fitting perfectly with the medium to provide a stronger, lasting impact.